2014
DOI: 10.1371/journal.pone.0094709
|View full text |Cite
|
Sign up to set email alerts
|

Who Has Used Internal Company Documents for Biomedical and Public Health Research and Where Did They Find Them?

Abstract: ObjectiveTo describe the sources of internal company documents used in public health and healthcare research.MethodsWe searched PubMed and Embase for articles using internal company documents to address a research question about a health-related topic. Our primary interest was where authors obtained internal company documents for their research. We also extracted information on type of company, type of research question, type of internal documents, and funding source.ResultsOur searches identified 9,305 citati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…We searched the Truth Tobacco Industry Documents Library, 32 which contains over 14 million related to the industry, between January and May 2018 using established snowball methods. [33][34][35][36][37][38] Original searches focused on keywords (e.g. tax differential, border store) combined with delimiters like the names of individual states.…”
Section: Methodsmentioning
confidence: 99%
“…We searched the Truth Tobacco Industry Documents Library, 32 which contains over 14 million related to the industry, between January and May 2018 using established snowball methods. [33][34][35][36][37][38] Original searches focused on keywords (e.g. tax differential, border store) combined with delimiters like the names of individual states.…”
Section: Methodsmentioning
confidence: 99%
“…While they are currently available upon request from the European Medicines Agency for drugs submitted for approval, the FDA does not make CSRs publicly available . Many CSRs are available through unsealed litigation documents and other sources . We recommend that you use CSRs when possible, even when trials have been reported in public sources (eg, journal articles), and that you search for and request CSRs from manufacturers for all trials of drugs, biologics, and medical devices.…”
Section: Step 1 Specify Which Sources You Will Use For Your Review Amentioning
confidence: 99%
“…Between June 2018 and July 2019, we searched the Truth Tobacco Industry Documents Library34 using established snowball methods 36–41. We began with ‘minimum price’ and ‘unfair cigarette sales’; searches were refined using names of states, corporate departments and employees, campaigns by date and materials identified from nearby documents using Bates numbers.…”
Section: Methodsmentioning
confidence: 99%